2018
DOI: 10.22232/stj.2018.06.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium Glutamate Toxicity and the Possible Protective Role of L–Carnitine

Abstract: Monosodium glutamate is naturally available non-essential amino acids, which found in naturally occurring foods and used as flavour enhancer worldwide. Monosodium glutamate is believed to be linked with diverse health problems. The aim of the study was toxic effects of monosodium glutamate (MSG) and the protective role of L-carnitine, light on the available literature from last 25 years about diverse toxicity studies which had been carried out on animal and human models. Google scholar, NCBI, PUBMED, EMBASE, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Antioxidants facilitate defense mechanism against oxidation of biomolecules such as lipid, nucleic acids and protein. Redox status of the cells can be measured using antioxidant enzymes (CAT, SOD and GSH) and the lipid peroxidation end product, MDA [4]. SOD mops up cellular superoxide anion and hinders the peroxidation of membrane lipid.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Antioxidants facilitate defense mechanism against oxidation of biomolecules such as lipid, nucleic acids and protein. Redox status of the cells can be measured using antioxidant enzymes (CAT, SOD and GSH) and the lipid peroxidation end product, MDA [4]. SOD mops up cellular superoxide anion and hinders the peroxidation of membrane lipid.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes et al [3] reported that administration of MSG at 4.0 mg/g for 120 days exhibited testicular, prostatic and epididymis dysfunction. MSG triggers hemorrhage in the testis, deterioration of sperm production and cell structure which ultimately results in male infertility [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excitatory amino acid carrier 1 (EAAC1) (intestine), glutamate/aspartate transporter 1 (GLAST1), and glutamate transport (GLT1) (stomach), respectively, are the primary glutamate and glutamine active transporters. These transporters are reliant on sodium ions and are competitively blockable [ 8 ]. Glutamate can be transformed into free amino acids in the gut, where they can subsequently be further metabolized [ 9 ].…”
Section: Introductionmentioning
confidence: 99%